Indonesian Undergraduate EFL Students’ Perceptions toward Flipped Classroom - Amanda Vira Maharani; Hamamah Hamamah; Ika Nurhayani (Edcomtech, 2020)
Abstract: The aim of this study was to find Indonesian undergraduate EFL students’ perceptions towards the implementation of flipped classroom. This study implemented survey research design and perceptions were found out through questionnaire and the questionnaires were spread to 30 students who experienced the implementation of flipped classroom. The questionnaire consisted of two aspects, namely meaningful and competence aspects. The results of questionnaire of perceptions were statistically calculated. The data on meaningful aspect revealed that mostly the students had positive perceptions toward the implementation of flipped classroom. On the other hand, in competence aspect, the students perceived that flipped classroom was beneficial for their writing competence. However, for the pre-class activities, such as viewing video and reading e-materials, the students had varied perceptions on it. They actually like the idea to have an additional video-lecture and e-material to prepare them before the class, but they did not really see the meaning by doing that pre-class activities. Tujuan dari penelitian ini adalah untuk menemukan persepsi mahasiswa EFL Indonesia terhadap penerapan flipped classroom. Penelitian ini menggunakan desain survey dan data dikumpulkan melalui kuesioner dan disebarkan kepada 30 siswa yang mengalami implementasi flipped classroom. Kuesioner terdiri dari dua aspek, yaitu aspek kebermaknaan dan kompetensi. Hasil kuesioner dihitung secara statistik. Data pada aspek kebermaknaan mengungkapkan bahwa sebagian besar siswa memiliki persepsi positif terhadap pelaksanaan flipped classroom. Di sisi lain, dalam aspek kompetensi, siswa merasa bahwa flipped classroom bermanfaat untuk kompetensi menulis mereka. Namun, untuk kegiatan pra-kelas, seperti menonton video dan membaca materi daring, siswa memiliki berbagai persepsi di dalamnya. Mereka menyukai ide untuk meononton video pengajaran dan materi daring tambahan untuk mempersiapkan mereka sebelum kelas, tetapi mereka tidak benar-benar melihat arti pada pelaksanaan kegiatan pra-kelas tersebut.